Which is a better predictor of plant traits: temperature or precipitation? - Moles, Angela T; Perkins, Sarah E; Laffan, Shawn W; Flores‐Moreno, Habacuc; Awasthy, Monica; Tindall, Marianne L; Sack, Lawren; Pitman, Andy; Kattge, Jens; Aarssen, Lonnie W; Anand, Madhur; Bahn, Michael; et al. (Journal of vegetation science, 2014)
QUESTION: Are plant traits more closely correlated with mean annual temperature, or with mean annual precipitation? LOCATION: Global. METHODS: We quantified the strength of the relationships between temperature and precipitation and 21 plant traits from 447,961 species‐site combinations worldwide. We used meta‐analysis to provide an overall answer to our question. RESULTS: Mean annual temperature was significantly more strongly correlated with plant traits than was mean annual precipitation. CONCLUSIONS: Our study provides support for some of the assumptions of classical vegetation theory, and points to many interesting directions for future research. The relatively low R² values for precipitation might reflect the weak link between mean annual precipitation and the availability of water to plants.